Efektivitas Net Interest Margin dan Loan to Deposit Ratio Terhadap Profitabilitas Perbankan - Hasbi, Hariandy; Djaniar, Upik; Putri, PA Andiena Nindya; Irdawati, Irdawati; Anantadjaya, Samuel PD (Universitas Nahdlatul Ulama Blitar, 2024)
This research examines the effectiveness of Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) on banking profitability. The study employs a quantitative approach using financial data from a sample of banks over a specific period. Through regression analysis, the study explores the relationship between NIM, LDR, and profitability indicators such as Return on Assets (ROA) and Return on Equity (ROE). The findings suggest a significant impact of NIM and LDR on banking profitability, indicating that these two factors play crucial roles in determining the financial performance of banks. Moreover, the study contributes to the existing literature by providing empirical evidence regarding the effectiveness of NIM and LDR in influencing bank profitability. Understanding these relationships is essential for bank management, policymakers, and stakeholders in making informed decisions related to financial performance and risk management. The results imply that banks should carefully manage their interest margins and loan-to-deposit ratios to enhance profitability and sustain long-term growth. The study underscores the importance of monitoring NIM and LDR dynamics as part of effective banking management strategies